Role of leptin in the pathogenesis of systemic lupus erythematosus - I Nyoman Suarjana (Indonesian Rheumatology Association, 2009)
Leptin is a 16 kDa adipocyte-secreted hormone that regulates weight centrally and links nutritional status to neuroendocrine and immune functions. Several studies indicate that leptin plays an important role in immune responses. Leptin affects both innate and adaptive immunity. It can stimulate dendritic cells (DC), monocytes, macrophages, neutrophils and natural killer cells. Leptin is involved in DC maturation and survival,and can skew the cytokine balance of a T helper (Th)1 profi le. In adaptive immunity, leptin can promote naÃ¯ve T cell survival and production of interferon-Î³ and interleukin-2, and activate Th1 cells while inhibiting Th2 cells. Leptin may play an important role in theregulation of the Th1/Th2 balance. As a survival factor, leptin has been shown to suppress B cell apoptosis. The role of leptin in the pathogenesis of systemic lupuserythematosus (SLE) is not fully determined yet. This review tries to link the role of leptin in immunity to the pathogenesis of SLE.